DOMESTIC TOURISTS’ REVISIT INTENTION TO MANGROVE TOURISM IN JAKARTA: A THEORY OF PLANNED BEHAVIOR APPROACH - Wiyana, Shabilla Maharani; Billa, Khaerun Nissa; Kurniawati, Kurniawati (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the factors influencing the revisit intention of domestic tourists to mangrove tourism destinations in the Jakarta area using the Theory of Planned Behavior (TPB) approach. The main focus is directed toward the influence of environmental knowledge, environmental advertising, and moral norms on tourists' attitudes, as well as the impact of these attitudes on revisit intention. This study utilizes a quantitative method, employing a cross-sectional survey approach involving 361 respondents who have visited mangrove tourism areas in Jakarta. The sampling technique used is purposive sampling, while data analysis is conducted using the Structural Equation Modeling (SEM) method with the assistance of AMOS software. Keywords: Green Marketing; Environmental Knowledge; Environmental Advertisement; Moral Norms; Attitude; Revisit Intention